Curcumin disturbed cell‐cycle distribution of HepG2 cells via cytoskeletal arrangement. Issue 4 (15th October 2012) - Jiang, Jinhuan; Jin, Hua; Liu, Li; Pi, Jing; Yang, Fen; Cai, Jiye
Summary Due to its extensive antitumor activity, curcumin has been focused on by more researchers. But, its antiproliferative mechanisms are still unknown. Here we studied the antiproliferative activity of curcumin in human liver cancer HepG2 cells. In order to analyze the cytotoxic activity and anticancer mechanisms of curcumin, we carried out cytotoxicity tests using 3‐[4, 5‐dimethyl‐2‐thiazolyl]‐2, 5 diphenyltetrazolium bromide (MTT) assay. The HepG2 cell cycle distribution and the expression of tubulin were detected by flow cytometry. Alterations in morphological and cytoskeletal properties of HepG2 cells were investigated using atomic force microscopy (AFM). Simultaneously, the effects of curcumin on the growth and proliferation of HepG2 cells were also assayed by MTT method. Cells were incubated with different doses of curcumin (0–80 μmol/l) for 24 h, the cell viability decreased from 91.10 ± 3.2% to 10.84 ± 4.0%, and the 50% inhibiting concentration (IC50) was 23.15 ± 0.37 μmol/l. Moreover, flow cytometry quantitatively detected that curcumin treatment resulted in a dose‐dependent accumulation of HepG2 cells in G2/M phase with concomitant losses from G0/G1 phase, so curcumin caused cell‐cycle arrest at G2/M phase. Furthermore, we discovered that curcumin was able to upregulate the expression of tubulin in HepG2 cells. In addition, AFM analysis including cell‐membrane structure and cytoskeleton networks is helpful to explain the relationship between the changes of cells and external pharmacologic stimulation. SCANNING 35: 253‐260, 2013. © 2012 Wiley Periodicals, Inc.